Uji Toksisitas Ekstrak Etanol Temu Blenyeh (Curcuma purpurascens Blume) terhadap Ikan Zebra (Danio rerio) - Dewi, Amaria; Pramiastuti, Oktariani; Nurhidayati, Lailiana Garna (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Toxicity testing is an initial step to evaluate the bioactivity of compounds that may exhibit toxic effects. In this study, zebrafish (Danio rerio) were used as the test animals. The rhizome of Curcuma purpurascens Blume is known to contain flavonoids, alkaloids, and tannins that potentially have toxic effects. The rhizome extract was standardized according to quality control tests. This study aimed to identify the toxic effects of the rhizome extract of Curcuma purpurascens and to determine its LC50 value. The toxicity test method used was acute toxicity testing in zebrafish, observing the mortality rate over a 96-hour period. Each aquarium contained 7 zebrafish, and the tested extract concentrations were 1000, 500, 250, 125, and 62.5 ppm. Mortality data were analyzed using the probit method with SPSS software to obtain the LC50 value, which represents the concentration that statistically causes 50% mortality of the test population within 24 hours. The results showed that the rhizome extract of Curcuma purpurascens exhibited toxic effects with an LC50 value of 83.7 ppm. This LC50 value falls within the toxic category based on toxicity test parameters. These findings indicate that the bioactive compounds in the rhizome extract, such as flavonoids, alkaloids, and tannins, which act as stomach poisons, cell proliferation inhibitors, and apoptosis inducers, can be toxic to normal human cells but may be useful in cancer treatment.